Applications and common coupled fixed point results in ordered partial metric spaces - KPR Rao; GNV Kishore; Kenan Tas; S Satyanaraya; D Ram Prasad (Fixed Point Theory and Applications, 2017)
Abstract In this paper, we obtain a unique common coupled fixed point theorem by using ( ψ , α , β ) $(ψ , α , β )$ -contraction in ordered partial metric spaces. We give an application to integral equations as well as homotopy theory. Also we furnish an example which supports our theorem.